2003
DOI: 10.1080/10584580390258327
|View full text |Cite
|
Sign up to set email alerts
|

New Approach to Analysis of the Switching Current Data, Recorded During Conventional Hysteresis Measurements

Abstract: The explanation of fatigue as a spatially non-uniform kinetic imprint due to evolution of the local threshold field distribution function has been proposed by us recently. In this paper we propose a new switching current analysis which allows to extract the distribution function from the data of conventional hysteresis loop measurements. Domain kinetics in slow-increasing field in spatially inhomogeneous ferroelectric was investigated by computer simulation. Domain arising and growth were considered under assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…It was assumed that in thin films the switching is limited by the nucleation of reversed domains rather than by the sidewise motion of domain walls; therefore the switching kinetics was described in terms of the distribution function of the nucleation probabilities. Another approach for investigation of the polarization reversal in inhomogeneous media was developed by the group of Shur [20,21]. It has been shown that analysis of the switching current data, recorded during quasi-static switching in slow increasing field, enables to extract the distribution function of the local internal bias fields and their evolution during polarization reversal in ferroelectric thin films.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…It was assumed that in thin films the switching is limited by the nucleation of reversed domains rather than by the sidewise motion of domain walls; therefore the switching kinetics was described in terms of the distribution function of the nucleation probabilities. Another approach for investigation of the polarization reversal in inhomogeneous media was developed by the group of Shur [20,21]. It has been shown that analysis of the switching current data, recorded during quasi-static switching in slow increasing field, enables to extract the distribution function of the local internal bias fields and their evolution during polarization reversal in ferroelectric thin films.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…It is seen that the switching charge decrease (i.e. fatigue) for a number of switching cycles larger than 1 × 10 5 (figure 2(b)) is followed by an essential increase of the halfwidth σ of the switching current peak versus applied voltage [23] measured during cycling (the decrease of 1/σ is shown in figure 4). The widening of the switching current peak reveals the growth of frozen domains in the ferroelectric film.…”
Section: Fatigue Mechanismsmentioning
confidence: 98%
“…The widening of the switching current peak reveals the growth of frozen domains in the ferroelectric film. A dependence of the dispersion on the number of cycles N for the fatigue stage has been recently proposed [23]:…”
Section: Fatigue Mechanismsmentioning
confidence: 99%
“…Such non-uniform bias field leads to the local variation of the switching time thus resulting in the observed heterogeneity of the switching characteristics in different regions of the sample. The heterogeneity of the local switching times is also the reason of observed tilting of the hysteresis loops [18,19].…”
Section: Characterizationmentioning
confidence: 99%